Anti –Inflammatory Activity of Propolis Trigona sp. Water Extract from North Lombok with Red Blood Cell Membrane Stability Method - Humaira, Ani Fatin; Aini, Siti Rahmatul; Hasina, Raisya (Biology, Medicine, & Natural Product Chemistry, 2024)
Propolis is a bee product that can be used as an anti-inflammatory. Cultivation of propolis-producing bees is also carried out in North Lombok. However, propolis has not been utilized optimally by the people of North Lombok. Apart from that, testing of North Lombok propolis is still limited to the chemical content and antioxidant activity of propolis extracted with ethanol solvent. Therefore, this study aims to determine the activity and effective concentration of North Lombok propolis water extract as an anti-inflammatory using the red blood cell membrane stability method. Groups include control groups such as positive control (diclofenac sodium), negative control (distilled water), and test groups (propolis water extract concentrations of 10%, 12.5%, 15%, 17.5%, 20%, 22.5%, 25%, 27.5%, and 30%). In The first step human blood was centrifuged of human blood, and then part of the red blood cells (sediment) was taken and saline was added to obtain a red blood cell suspension. Next, mixing the test solution was carried out in the order of 0.5 ml of red blood cell suspension, then 0.5 ml of extract was added (0.1% w/v Na-diclofenac solution in the positive control, distilled water in the negative control), 1 mL of buffer solution and 2 mL of hyposaline solution, then homogenized. Each group was incubated at 37°C for 30 minutes, then centrifuged for 10 minutes at 3000 rpm. The supernatant was taken, and the absorbance was read with a UV-Vis spectrophotometer at 560 nm. Next, the percentage value of red blood cell hemolysis protection was calculated. The data obtained were tested statistically using One-way ANOVA and post-hoc (LSD) tests SPSS version 29. The results showed that propolis water extract concentrations were 10%, 12.5%, 15%, 17.5%, 20%, 22.5%, 25%, 27.5%, and 30% have anti-inflammatory activity because they can increase the stability of the red blood cell membrane with a percentage of hemolysis protection of respectively 57.92%, 59.99%, 60.99%, 61.99%, 64.31%, 69.59%, 75.07%, 79.77% and 84.45%. Propolis water extract concentrations of 10%, 12.5%, 15%, 17.5%, 20%, 22.5%, and 25% had anti-inflammatory effects that were not significantly different from the positive control (p>0.05). The 27.5 % and 30% concentrations had a higher percent hemolysis protection value than the positive control (p<0.05).